Spatiotemporal patterns in precipitation whiplash over China during 1901–2100 based on CMIP6 simulations - Honghao Luo; Nergui Nanding; Fuying Deng; Huan Wu; Zhijun Huang; Junxu Chen; Jiabin Peng; Bin Zhang (Environmental Research Communications)
The increasing risk of precipitation whiplash, characterized by rapid transitions between extreme drought and wet conditions, is largely related to atmospheric circulation changes due to anthropogenic greenhouse gas emissions. This study aims to examine the changing patterns of precipitation whiplash events for future projections (2021–2100) with regard to the current climate (1981–2020), and to unveil the relations between intensity, duration, and frequency of these events for various return periods across different regions of China. Multi-source observational datasets were also used to analyze the trend of precipitation whiplash indices for the current climate and to assess the ability of the CMIP6 ensemble model for reproducing the characteristics of precipitation whiplash events. The Intensity-Duration-Frequency (IDF) curves were estimated by using the nonstationary Generalized Extreme Value (GEV) model combined with Bayesian inference. The results show an increasing trend in frequency, intensity, and severity of precipitation whiplash events, particularly for the long-term future, while the duration of these transitions shows a decreasing trend. The peak occurrence months during the long-term future period exhibit notable changes in most parts of China. Specifically, the dry-to-wet whiplash events occur approximately two months earlier than in the current period, while the wet-to-dry whiplash occurs approximately two months later. The results also indicated that IDF curves shifted upward, particularly in the long-term future projections, suggesting an increased likelihood of more severe events. The findings of this study will serve as an essential reference for local authorities to develop more effective water resource management and disaster mitigation policies to tackle the impact of future climate change.